Skill, Transformational Leadership, And Competitiveness: Relationships In A Love Triangle - Tegor, Tegor; Johannes, Johannes; Jaya, R Indra Kusuma; Thasimmim, Said Nuwrun (JURNAL AL-TANZIM, 2023)
This study aims to see the extent to which transformational leadership plays a role in mediating the relationship between personal skills and the competitiveness of private employees in the Karimun district. The total population used was 75 respondents selected based on random sampling techniques. Data analysis techniques use Smart PLS, and the results of this study are: 1) Skills have a direct and significant effect on competitiveness; skills possessed by employees can help increase the competitiveness of companies in a competitive market. 2) Skills have a significant influence on transformational leadership. Good skills can help a leader to set a good example, provide clear direction, motivate the team, solve problems, and build good relationships with his team members. 3) Transformational leadership has a significant positive impact on the company’s competitiveness. Transformational leadership can help increase productivity, drive innovation, increase employee satisfaction, and improve company reputation and competitiveness. 4) Skills have a direct and significant effect on competitiveness through transformational leadership. Skills can help increase productivity, drive innovation, increase employee satisfaction, improve a company's reputation, and enhance a company's overall competitive ability.